Pura Dalem Betawi: Harmonisasi Komunikasi Antarbudaya Dalam Ikatan Menyamabraya Hindu dan Budha - Pramesti Dasih, I Gusti Ayu Ratna; Padawati Indraswari, I Gusti Ayu Diah Prameswara (Jurnal Penelitian Agama Hindu, 2023)
Pura Dalem Betawi is located in Banjar Jumpayah, Mengwitani Village, Mengwi Subdistrict, Badung Regency, Bali Province, belonging to the concept of siwa-buddha. The uniqueness of Pura Dalem Betawi is the palinggih Gedong Buddha Dewi Kwan Im, and its piodalan coincides with Chinese New Year. The community as the temple caretakers call it Chinese New Year piodalan. Intercultural interaction occurs at Pura Dalem Betawi, because the Chinese New Year piodalan is attended by Chinese people. The purpose of this research emphasizes the context of intercultural communication, namely to bridge the process of community interaction in ethnic, religious and racial differences, so that social conflict does not arise. The research used a qualitative-interpretative approach with the intention of exploring information that describes the existence of the research location, based on community experience and describing it in scientific work. Determination of informants using purposive sampling technique, with the consideration that the informants know and understand the research topic, such as: pemangku, pengempon temple, religious leaders, and temple pengayah from Chinese residents. The data analysis technique uses the Miles and Huberman model, resulting in a picture that intercultural communication has a very important role in the process of social interaction in Pura Dalem Betawi. The intercultural communication approaches applied are: social psychological, intercreative, and cultural dialogic approaches. Humans develop understanding through their mindset, and gain new knowledge through interaction so that they can interpret it to form perceptions. The intercultural communication approach is combined with the concept of menyamabraya that has been inherent in Balinese life. Menyamabraya is ideal, because it views all humans as brothers, so menyamabraya is applied in intercultural interactions at Pura Dalem Betawi when ngayah prepares for the Chinese New Year piodalan. Cultural acculturation in Pura Dalem Betawi runs harmoniously and in line with religious moderation, because it has the same goal in maintaining harmony.